ANALISIS PENGARUH BEBAN GEJALA TERHADAP KUALITAS HIDUP ANAK KANKER YANG MENJALANI KEMOTERAPI - Devi, Ni Luh Putu Shinta; Lestari, Made Pande Lilik; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 12 No 1 (2024): Februari 2024, 2024)
Children with cancer can experience various problems both physically and psychologically. The high symptom burden experienced by children can cause children to feel depressed and can affect the children’s quality of life. This study aimed to see the influence of symptom burden in children’s quality of life. This study used descriptive correlative design with a cross sectional approach. The research was conducted in the pediatric ward at Prof. I.G.N.G Ngoerah Hospital. The sample in this study was 32 children who were selected using a purposive sampling technique. The data collected in this study included demographic data of respondents, child’s symptom burden assessed using the Memorial Symptom Assessment Scale (MSAS) (7-12) and children’s quality of life assessed using the PedsQL 3.0 Cancer Module. Data analysis was performed by simple linear regression. It was found that there was a significant relationship between symptom burden and the quality of life children with cancer (p=0.00005; ?=0.05). Symptom burden and quality of life had a strong relationship (r=0,685) and had a negative pattern. Symptom burden was also found to affect children's quality of life by 46,9%.